Image 1_Forgoing Healthcare and Insurance Premiums Trends: A 15-Year Population-Based Study in Geneva, Switzerland.png - Mayssam Nehme (10232172) (2025)
Objectives Despite compulsory universal health coverage, rising health insurance premiums in Geneva, Switzerland may present financial barriers to care. This study evaluates trends in forgoing healthcare for financial reasons from 2011 to 2025, with associations with insurance premiums, socioeconomic and health-related factors. Methods We conducted an annual cross-sectional study with 1,000 randomly selected participants every year (2011–2025), (n = 10,169). The primary outcome was self-reported forgoing of healthcare for financial reasons. Temporal trends and associations with premiums were analyzed using Locally Estimated Scatterplot Smoothing LOESS regression. Logistic regression assessed associations with individual-level determinants. Results Overall, 18.1% reported forgoing care, increasing from 15.8% in 2011 to 25.8% in 2025 (+64.6%), corresponding to a 61.9% rise in premiums. Although low income remained a strong predictor (aOR 2.33 [1.76–3.09]), increases were also seen among higher-income groups. Strong correlations were found between premiums and forgoing care, especially in women (0.813) and young adults (0.805). Conclusion Additional reforms are needed to reduce growing inequities in access to care despite compulsory universal coverage.